Draft Genome Sequence of the Earthworm Eudrilus eugeniae - Arumugaperumal, Arun; Sudalaimani, Dinesh K.; Arumugaswami, Vaithilingaraja; Sivasubramaniam, Sudhakar (Current Genomics, 2022)
Background: Earthworms are annelids. They play a major role in agriculture and soil fertility. Vermicompost is the best organic manure for plant crops. Eudrilus eugeniae is an earthworm well suited for efficient vermicompost production. The worm is also used to study the cell and molecular biology of regeneration, molecular toxicology, developmental biology, etc., because of its abilities like high growth rate, rapid reproduction, tolerability toward wide temperature range, and less cost of maintenance. Objective: The whole genome has been revealed only for Eisenia andrei and Eisenia fetida. Methods: In the present work, we sequenced the genome of E. eugeniae using the Illumina platform and generated 160,684,383 paired-end reads. Results: The reads were assembled into a draft genome of size 488 Mb with 743,870 contigs and successfully annotated 24,599 genes. Further, 208 stem cell-specific genes and 3,432 non-coding genes were identified. Conclusion: The sequence and annotation details were hosted in a web application available at https://sudhakar-sivasubramaniam-labs.shinyapps.io/eudrilus_genome/.
Keywords: genome resource